International migration in the age of crisis and globalization : historical and recent experiences - Solimano, Andres (New York : Cambridge University Press, 2010)
"The international mobility of people and elites is a main feature o f the global economy of today and yesterday. Immigration augments the l abor force in receiving countries and provides many of the bodies and m inds that are essential to any vibrant economy. Talented people are cri tical to the transfer of knowledge, ideas, fresh capital, contacts, and entrepreneurial capacities. This book is based on a blend of theory, v aried country examples, and rich historical material ranging from the m id-nineteenth century to the early twenty-first century. It discusses t he conceptual underpinnings of the push and pull factors of current mig ration waves and their impacts for development on the source and receiv ing countries. The analysis reviews the historical context under which various migration experiences have taken place - both in periods of int ernationalism and in periods of nationalism - in order to contribute to debates on the desirability of and tensions and costs involved in the current process of international migration and globalization. These iss ues are relevant during both times of economic slumps and times of econ omic growth"--Provided by publisher.
"The international mobility of people is a main feature of the globa l economy of today and yesterday although external openness is oft en m ore favorable to goods and money than people across diff erent periods of the world economy including crisis, globalization, nationalism and a utarkic trends. Immigration augments the labor force in receiving count ries and provides many of the bodies and minds that are essential to an y vibrant economy. Talented people are critical to the transfer of know ledge, ideas, fresh capital, contacts, and entrepreneurial capacities. Th is book that promotes a freer and more humane regime for the mobilit y of people is based on a blend of theory and empirical evidence compri sing varied country examples, and rich historical material ranging from the mid-19th century to the early 21st century. It discusses the conce ptual underpinnings of the push-and-pull factors of current migration w aves and their impacts for development on the source and receiving coun tries. Th e analysis reviews the historical context under which various migration experiences have taken place - both in periods of internatio nalism and in periods of nationalism - in order to contribute to debate s on the desirability of and the tensions and costs involved in the cur rent process of international migration and globalization. Th ese issue s are relevant during times of both economic slumps and times of econom ic growth"--Provided by publisher.
Machine generated contents note: 1. Introduction: understanding the trends, themes, and strata of international migration; 2. Why people mo ve or stay put: international migration is the result of compelling and conflicting factors; 3. What happens when international migration happ ens? The dilemmas posed by migration; 4. How empires, policy regimes, a nd economic imperatives influenced the mobility of capital and people i n the 20th century; 5. Latin America: where volatile economic developme nt, political crises, poverty, and remittance income is a laboratory fo r studying the determinants of international migration; 6. Who migrates and what they offer: a focus on people and elites with talent, knowled ge, and entrepreneurial skills; 7. International migration requires tha t the global community put it effectively on its agenda.
Includes bibliographical references and index.
Keywords: Emigration and immigration; Emigration and immigration -- Economic aspects